An efficient cell vertex method for unstructured tetrahedral grids - Crumpton, P (Proceedings of the 1995 ICFD conference at Oxford, 1995)
This paper introduces an efficient Euler solver for large tetrahedral grids (6,700,000 cells). The underlying method is a cell vertex finite volume formulation with a Lax--Wendroff pseudo time--stepping update. This is used as a smoother in an unstructured multigrid method, which requires a sequence of non--nested tetrahedral grids. Fast solutions are achieved by using a distributed memory parallel computer.